Basil (Ocimum basilicum L.) harvest and plant replacement methods in aquaponia - Lelesz, Judit Éva; Virág, István Csaba (Acta Agraria Debreceniensis, 2023)
The aim of the study is to investigate the potential of basil leaf mass production under aquaponic conditions with different harvest and plant replacement methods. Aquaponics is a combination of soil-less crop production hydroponics and aquaculture and it is can use and clean the wastewater of intensive aquaculture systems. Three groups were established in the 6 units during the six-week harvest and seedling rotation cycles. Group 1 individuals remain in the units throughout the breeding season. Group 2 individuals were replaced every 12 weeks, while Group 3 individuals were replaced every six weeks, at the same time as harvest. Data from the experiment were analysed to determine how the harvest and replacement protocol of basil plants influences the amount of leaves harvested, the percentage of leaves harvested relative to the plant stem, and the changes in plant height, SPAD and NDVI during harvest and replacement. A continuously maintained and harvested healthy basil stock under aquaponic conditions can provide a consistent leaf mass all year round without the extra cost of replacing and producing seedlings.